Maximizing ELSA Speak for Developing English Fluency and Reducing Speaking Barriers in Language Learners - Annisa Qatrunnada Mardiah; Saadillah (English Language Education, Universitas Internasional Batam, 2025)
Many language learners face challenges in developing English speaking fluency, including mispronunciation, limited vocabulary, and low self-confidence. This study examines the effectiveness of the ELSA Speak application in improving speaking skills and reducing speaking barriers. Using an Explanatory Sequential Design, the research includes a quantitative phase followed by a qualitative phase. In the quantitative phase, students took pre-tests and post-tests to measure progress. Results showed significant improvement, especially in pronunciation. The qualitative phase involved interviews to explore students’ experiences using the app. Findings revealed increased confidence, reduced anxiety, and positive responses to the app’s real-time feedback and pronunciation correction features. Despite minor technical issues, students found ELSA Speak engaging and helpful for independent practice. The study concludes that ELSA Speak is an effective tool for enhancing fluency and addressing speaking difficulties. These results suggest that digital applications can support traditional language learning by providing structured and interactive speaking practice.